Flash boys : a Wall Street revolt - Lewis, Michael (Michael M.) (W.W. Norton & Company, 2014)
A small group of Wall Street guys who figure out that the U.S. stock market has been rigged for the benefit of insiders at the big Wall Street banks expose this institutionalized injustice and go to war to fix it.